Barriers and success factors to the implementation of a multi-site prospective adverse event surveillance system - Backman, C.; Forster, A. J.; Vanderloo, S. (Université d'Ottawa | University of Ottawa, 2014)
Objectives. To determine the feasibility of implementing a clinical observation method for adverse event detection. Methods. Prospective adverse event surveillance was conducted from February to April 2012. We implemented this adverse event prospective surveillance system on the general internal medicine units of five sites within two teaching institutions and one community hospital. Following surveillance, we assembled provider and decision-maker focus groups to understand the barriers and success factors related to our implementation. We used a structured interview guide with facilitated discussion. Results. We performed six focus group interviews in June and July 2012. In total, 31 individual participated including senior executives (15), managers (7) and care providers (9). We identified the following success factors: the overall design of the system including the clinical observer and clinical reviewer functions; the credibility of the data and the opportunity to make changes to practice in ‘real-time’. We identified the following opportunities for improvement: the need for clear guidelines on the type of in- formation to collect for each event trigger, and for an action plan to ensure accountability and follow through on improvement efforts once the adverse event data have been analyzed. Conclusions. This work supports a conclusion that prospective surveillance is viewed as beneficial and acceptable. For this reason, healthcare organizations should consider adopting prospective adverse event surveillance to support their local quality improvement methods.
Keywords: prospective surveillance; safety management/methods; sentinel surveillance; Data Collection; Humans; Program Evaluation; Prospective Studies; Quality Improvement; Quality Indicators, Health Care; Safety Management; Health Facility Administration